EFEKTIVITAS PENERAPAN REDD+ DI KALIMANTAN BARAT REGULASI DAN CAPAIAN PENGURANGAN EMISI - NIM. A1012211017, DIMAS GALIH WICAKSANA (Jurnal Fatwa Hukum, 2025)
Abstract  The global climate crisis, driven by rising greenhouse gas (GHG) emissions from human activities, poses a severe threat to humanity. Deforestation and land-use change, particularly in forest-rich countries like Indonesia, are major contributors to these emissions. Conflicts over forest management between indigenous communities, government authorities, and private companies further exacerbate the issue. Indonesia, as the world"™s eighth-largest GHG emitter, has committed to reducing emissions through the Paris Agreement, ratified in 2016. This study examines the REDD+ (Reducing Emissions from Deforestation and Forest Degradation) regulatory framework at international, national, and West Kalimantan provincial levels, and its implementation in West Kalimantan, focusing on effectiveness, challenges, and barriers.Using a juridical approach and literature review supported by interviews, this study is based on the theory of treaty ratification under the UNFCCC and Paris Agreement, Anthony Allott"™s theory of legal effectiveness, and the REDD+ mechanism. The findings indicate that REDD+ regulations are governed internationally by the UNFCCC through COP decisions, including the Paris Agreement, and nationally by laws such as Law No. 6 of 1994 and Law No. 16 of 2016. West Kalimantan has adapted these regulations through local policies like Governor Regulation No. 125 of 2020.REDD+ implementation in West Kalimantan has shown partial effectiveness, with progress facilitated by institutional support and international partnerships. However, challenges such as limited public understanding, funding constraints, unresolved agrarian conflicts, and inadequate community involvement hinder its success. Respect for indigenous rights, equitable benefit-sharing, and community-based approaches are critical to REDD+"™s sustainability. Without these measures, REDD+ risks exacerbating social inequality and becoming a tool for greenwashing instead of a genuine climate solution.                 Keywords: REDD+, climate change, greenhouse gas emissions, forest management conflicts, indigenous rights, West Kalimantan.  Abstrak                 Krisis iklim global yang dipicu oleh peningkatan emisi gas rumah kaca (GRK) dari aktivitas manusia menjadi ancaman serius bagi umat manusia. Deforestasi dan perubahan penggunaan lahan, terutama di negara-negara kaya hutan seperti Indonesia, merupakan penyumbang utama emisi ini. Konflik pengelolaan hutan antara masyarakat adat, pemerintah, dan perusahaan swasta semakin memperburuk situasi. Indonesia, sebagai penghasil emisi GRK terbesar kedelapan di dunia, telah berkomitmen untuk mengurangi emisi melalui Perjanjian Paris yang diratifikasi pada tahun 2016. Penelitian ini mengkaji kerangka regulasi REDD+ (Reducing Emissions from Deforestation and Forest Degradation) di tingkat internasional, nasional, dan provinsi Kalimantan Barat, serta implementasinya di Kalimantan Barat dengan fokus pada efektivitas, tantangan, dan hambatan.               Menggunakan pendekatan yuridis dan studi pustaka yang didukung wawancara, penelitian ini didasarkan pada teori ratifikasi perjanjian internasional di bawah UNFCCC dan Perjanjian Paris, teori efektivitas hukum Anthony Allott, dan mekanisme REDD+. Hasil penelitian menunjukkan bahwa regulasi REDD+ diatur secara internasional oleh UNFCCC melalui keputusan COP, termasuk Perjanjian Paris, dan secara nasional melalui UU No. 6 Tahun 1994 dan UU No. 16 Tahun 2016. Kalimantan Barat menyesuaikan regulasi nasional tersebut melalui kebijakan lokal seperti Pergub No. 125 Tahun 2020.               Implementasi REDD+ di Kalimantan Barat telah menunjukkan efektivitas parsial, dengan dukungan kelembagaan dan kemitraan internasional yang mendorong kemajuan. Namun, tantangan seperti pemahaman masyarakat yang terbatas, kendala pendanaan, konflik agraria, dan rendahnya keterlibatan masyarakat dalam tahap perencanaan dan implementasi menghambat keberhasilannya. Pengakuan hak masyarakat adat, pembagian manfaat yang adil, dan pendekatan berbasis komunitas menjadi kunci keberlanjutan REDD+. Tanpa langkah ini, REDD+ berisiko memperburuk ketimpangan sosial dan menjadi instrumen greenwashing alih-alih solusi iklim yang nyata.               Kata Kunci: REDD+, perubahan iklim, emisi gas rumah kaca, konflik pengelolaan hutan, hak masyarakat adat, Kalimantan Barat.